Clinical characteristics of patients with COVID-19 depending on the treatment received and the presence of type 2 diabetes mellitus - K. G. Lobanova; T. Y. Demidova; S. N. Perekhodov; M. B. Antsiferov (Сахарный диабет)
BACKGROUND. Type 2 diabetes mellitus (T2DM) is an independent risk factor for adverse clinical outcomes in patients with Covid-19. There is currently insufficient data evaluating the efficacy and safety of drugs for the treatment of COVID-19, especially in patients with T2DM.AIM. The aim of study was to identify an associative relationship between the drugs used and the clinical outcomes of patients with Covid-19 and T2DM.MATERIALS AND METHODS. A retrospective analysis of the clinical outcomes of 1753 patients with COVID-19 who were hospitalized to the redesignated departments of multidisciplinary city clinical hospital in the period from 23.03.2020 to 01.06.2020.RESULTS. The total number of patients is 1,753, of which 311 (17.7%) are patients with DM2. 92.6% of patients received treatment for COVID-19. At the same time, 91.4% of patients received antibiotics (a/b), 61.5% — bronchodilators, 56.6% — injectable anticoagulants (a/c), 45.2% — hydroxychloroquine, 6.3% — antiviral drugs, 5.4% — oral a/c, 4.6% — glucocorticosteroids (GCS), 1.9% — Tocilizumab.Decrease of risk of death among patients with COVID-19 was as the therapy of a/b (OR 0.07, 95% CI 0.05–0.11, p<0.05), bronchodilators (OR 0.12, 95% CI 0.08–0.18, p<0.05) and injection a/c (OR 0.47, 95% CI 0.34–0.67, p<0.05). At the same time, among patients with DM2, compared with patients without DM2, there was a more pronounced reduction in the risk of death during injectable a/c therapy: among patients with DM2, the risk of death decreased by 2.6 times (OR 0.39, 95% CI 0.21–0.73, p<0.05), among patients without DM2 — by 2.1 times (OR 0.47, 95% CI 0.31–0.71, p<0.05). Antiviral drugs was associated with an increased chance of death among patients without DM2 (OR 2.64, 95% CI 1.44–4.86, p<0.05) and among patients with DM2 (OR 4.98, 95% CI 2.11–11.75, p<0.05).CONCLUSION. A significant decrease of the risk of death among patients with COVID-19 was as the therapy of a/b, bronchodilators, and injectable a/c. An increase of the risk of death was observed during therapy with antiviral drugs.